'For me it's about not feeling like I'm on a diet': a thematic analysis of women's experiences of an intermittent energy restricted diet to reduce breast cancer risk. Issue 6 (21st June 2018) - Donnelly, L. S.; Shaw, R. L.; Pegington, M.; Armitage, C. J.; Evans, D. G.; Howell, A.; Harvie, M. N.
Abstract: Background: Weight‐loss programmes requiring intermittent energy restriction offer an alternative to continuous energy restriction programmes that typically have low adherence. We reported greater weight loss, better adherence and spontaneous reduced energy intake on healthy eating days with intermittent as opposed to continuous energy restriction. The present study aims to explore why intermittent energy restriction diets exert these positive effects. Methods: Semi‐structured interviews were carried out with 13 women aged 39–62 years, who followed a 4‐month intermittent energy restriction (2 days of low energy/low carbohydrate, 5 days of healthy eating). Nine of the 13 women successfully lost >5% of their total body weight. Data were analysed using thematic analysis. Results: The intermittent regimen redefined the meaning of dieting and normal eating. Women reconceptualised dieting as only two low energy days per week, even though this often differed from their pre‐diet eating patterns. Women reported that they could adhere more closely to the rules of the intermittent diet compared to previously attempted continuous diets. They found that the intermittent diet was less cognitively demanding because the restrictive and clear rules of the intermittent diet were easier to understand and easier to follow than with continuous dieting. Conclusions: Many participants found intermittent dieting preferable to previous experiences of continuous dieting. The findings provide some insight into the ways in which intermittent dieting is successful, and why it could be considered a viable alternative to continuous energy restriction for weight loss.